Efeitos do treinamento muscular respiratório com diferentes modalidades em pacientes com Doença Pulmonar Obstrutiva (DPOC) - ensaio clínico aleatório controlado - Farias, Catharinne Angélica Carvalho de (2018)
Introduction: Respiratory Muscular Training (RMT) in patients with Chronic Obstructive Pulmonary Disease (COPD), does not yet have consensus about the effects that could add to Pulmonary Rehabilitation (PR). Objective: Our objective was to propose a PR protocol associated with different RMT modalities and to evaluate its additional effects on primary endpoints of exercise capacity and dyspnea in individuals with COPD. Methods: This was a blinded randomized clinical trial composed of patients diagnosed with COPD randomly assigned to three groups: Pulmonary Rehabilitation (PR), PR associated with inspiratory muscle training with conical flow resistance load (PR+RMTCFR) and PR associated with RMT endurance modality by normocapnic hyperpnea (PR+RMTNH). The protocol lasted 10 weeks, with a frequency of 3 supervised weekly and 2 days without supervision, composed of health education, energy conservation techniques, individual aerobic training on treadmill with a load of 70% of the maximum speed reached in the incremental test and peripheral muscle strengthening for all groups. The PR+RMTCFR group underwent training with an initial load of 35% of maximal inspiratory pressure (MIP) obtained in the initial evaluation with 5% progressions each week, up to a limit of 80% of MIP, reassessed and adjusted weekly. The PR+RMTNH group underwent training with a rehousing pocket equivalent to 50% of vital capacity, a respiratory rate of 35 times the value of forced expiratory volume in the first second, with increments of 2 to 3 minutes per week, until the maximum time of 20 minutes. The anthropometric characteristics, pulmonary function, respiratory muscle strength and endurance (MIP, SMIP, SNIP, MEP and MVV), exercise capacity (6MWT and ISWT), thoracic wall volumes in the endurance test, peripheral muscle strength, dyspnea and fatigue (BORG0-10), health status (CAT), risk of exacerbation and mortality of the subjects (BODE), before and after the intervention period. Statistical analysis was performed using the Shapiro-Wilk test, Anova One-way, Chi square and Anova Two-way with Bonferroni Pos hoc, according to the data distribution. A p <0.05 was considered and GraphPad Prism, 6.0 software was used. Results: A total of 34 subjects were evaluated and 33 patients (51.5%), 66.2 (± 4.9) years and BMI 28.0 (± 4.3) kg / m2 were evaluated. In the primary outcomes, we found, after 10 weeks, increased exercise capacity in the PR+RMTCFR and PR+RMTNH (p˂0.0001) groups, and in the intergroup analysis, the PR+RMTNH group was higher in the ISWT group RP (Pos hoc of p <0.005). We also found a reduction in the sensations of dyspnea and fatigue after 6MWT and ISWT, in all three groups (p <0.001), with no difference between them. In addition, there was an increase in PImax in all groups (p <0.0001), in SPImax only in the PR+RMTCFR group (p <0.0001) and improvement in SNIP in the groups that performed PR+RMT, with p<0.0001. In the PR+RMTNH group we observed an improvement in MEP (p<0.0001) with Pos hoc of 0.004 in relation to the PR group, and in the manual grip strength (p˂0.0001). It was also verified that in all three groups, there was a reduction in the risk of mortality (p˂0.0001), with an improvement in the health status in PR+RMTNH (p<0.001). The PR+RMTCFR group presented a reduction in the risk of exacerbation (p=0.0006) and an improvement in CAT (p=0.0001). Conclusions: The association of RMT to PR programs provided additional gains on exercise capacity, health status, respiratory and peripheral muscle strength, and the benefits found in all groups with reduced risk of exacerbation, mortality, dyspnea and fatigue. Although we can´t differentiate which RMT modality was superior, we believe that PR should be emphasized and RMT added to PR in future programs for this population.